Performances dell'Apocalisse nella letteratura e nel cinema postmoderno (Mantichora. Italian Journal of Performance Studies, 2020)
This paper observes the relationship between word and image, literature and cinema into the description and the visualization of the cultural object of Apocalypse in Postmodernism. Literature and cinema are able to exceed their own writing and visual limits in a complementary way. Trough narrative fiction examples – Pynchon’s Gravity’s Rainbow and DeLillo’s White Noise and Underworld – postmodern literature generates cinematographic performances to represent Apocalypse. On the other hand, through the rhetorical strategy of reboot, cinema writes and rewrites itself and its well-known apocalyptic sagas just like Romero’s Diary of Dead and Kelly’s Southland Tales do. These cultural practices use performative language exchanges to represent something of unspeakable and unimaginable like Apocalypse.